Mental Training and its Reflection on the Levels of Psychological Pregnancy from the Viewpoint of Football Players - Arabi , cheikh; Beneddine , Kamel (sports creativity, 2025)
The study aimed to highlight the reflection of mental training on psychological pregnancy from the point of view of football players, where the sample (42) included players from some teams of the department among the south-west associations the sample was selected in the intended way. The descriptive curriculum was adopted as a method of study, and the psychological burden of Kamel Abboud Hussein was used after adapting some of his phrases. In addition to the mental training questionnaire. The study concluded that there is a strong relationship between mental training and psychological pregnancy from the point of view of the players and as well as the average level of psychological load in the sample of the study and this is the result of the full attention of the skill of mental training as it is the main pillar in success and achieving the best results.